Uncomplicated acute appendicitis in situs inversus totalis. A case report - Saavedra Idrogo , Franklin (2023)
Introduction: Situs inversus totalis is a rare congenital malformation, characterized by an inverted position of the thoracic and abdominal organs, negatively influencing the diagnostic approach and surgical treatment. Report: Acute appendicitis was diagnosed in a 28-year-old male patient who knew his anatomical abnormality and was corroborated with tomographic images and laparoscopic exploration. He was admitted to the emergency room with 30 hours of abdominal pain with onset in the epigastrium and subsequent radiation to the left iliac fossa. The tomography confirmed his condition of situs inversus totalis and pathological signs in localized appendicitis in FII; The laparoscopic intervention was performed without complications. Discusions: In patients with pain in the left lower quadrant, an adequate differential diagnosis is important and prior knowledge of an anatomical abnormality communicated in a timely manner, that makes feasible an adequate diagnosis and successful surgical resolution.